Chick & Chickie play all day! : a Toon Book - Ponti, Claude, 1948- (New York : TOON Books, 2012)
Young chicks, Chick and Chickie, have fun making masks and playing with the letter A.
Booklist, April 2012
0.7
K-3
210L
F
Keywords: Chickens -- Comic books, strips, etc. -- Fiction; Play -- Comic books, strips, etc. -- Fiction; Chickens -- Juvenile fiction; Play -- Juvenile fiction; Cartoons and comics; Graphic novels; Readers (Elementary); Graphic novels; Comics (Graphic works)